2012
DOI: 10.1007/s00128-012-0891-5
|View full text |Cite
|
Sign up to set email alerts
|

Transcript Pattern of Cytochrome P450, Antioxidant and Ginsenoside Biosynthetic Pathway Genes Under Heavy Metal Stress in Panax ginseng Meyer

Abstract: The differential transcript patterns of five antioxidant genes, four genes related to the ginsenoside pathway and five P450 genes related to defense mechanism were investigated in in vitro adventitious roots of Panax ginseng after exposure to two different concentrations of heavy metals for 7 days. PgSOD-1 and PgCAT transcription increased in a dose-dependent manner during the exposure to CuCl(2), NiCl(2), and CdCl(2), while all other tested scavenging enzymes didn't show significant increase during heavy meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…In ginseng plants, among reported ginseng CYP genes (Balusamy et al, 2013;Devi et al, 2011), three CYP genes are involved in ginsenoside biosynthesis, CYP716A47 acts as protopanaxadiol synthase (PPDS) hydroxylating dammarenediol-II at the C-12 position, yielding PPD ; two additional CYP716A subfamily members: CYP716A53v2 as the protopanaxadiol 6-hydroxylase (or called protopanaxatriol synthase, PPTS), catalyzing the generation of PPT from PPD for the synthesis of dammarene-type ginsenosides in P. ginseng , CYP716A52v2 (oleanolic acid synthase, OAS) acting as a β-amyrin 28-oxidase modifying β-amyrin into oleanolic acid for the synthesis of an oleanane-type saponin in P. ginseng (Han et al, 2013). PPDS and PPTS express ubiquitously in all ginseng organs, and the expression of PPDS is promoted by MJ in adventitious roots, but neither for PPTS and OAS .…”
Section: Cytochrome P450mentioning
confidence: 99%
“…In ginseng plants, among reported ginseng CYP genes (Balusamy et al, 2013;Devi et al, 2011), three CYP genes are involved in ginsenoside biosynthesis, CYP716A47 acts as protopanaxadiol synthase (PPDS) hydroxylating dammarenediol-II at the C-12 position, yielding PPD ; two additional CYP716A subfamily members: CYP716A53v2 as the protopanaxadiol 6-hydroxylase (or called protopanaxatriol synthase, PPTS), catalyzing the generation of PPT from PPD for the synthesis of dammarene-type ginsenosides in P. ginseng , CYP716A52v2 (oleanolic acid synthase, OAS) acting as a β-amyrin 28-oxidase modifying β-amyrin into oleanolic acid for the synthesis of an oleanane-type saponin in P. ginseng (Han et al, 2013). PPDS and PPTS express ubiquitously in all ginseng organs, and the expression of PPDS is promoted by MJ in adventitious roots, but neither for PPTS and OAS .…”
Section: Cytochrome P450mentioning
confidence: 99%
“…The content of ginsenosides was higher in the storage roots of American ginseng plants in draughty condition compared with controls well supplied with water, implying that drought stress may induce the synthesis of ginsenosides . Various ginsenoside biosynthetic pathway‐related genes (e.g., PgSQE , PgDDS , and Pgβ‐AS ) were highly responsive to heavy metal stress in Panax ginseng …”
Section: Chemical Defense Role Of Ginsenosides In Plantsmentioning
confidence: 99%
“…32 Various ginsenoside biosynthetic pathwayrelated genes (e.g., PgSQE, PgDDS, and Pg -AS) were highly responsive to heavy metal stress in Panax ginseng. 33 Ginsenosides have been found to play a crucial defense role against biotic factors, such as insects and microorganisms. It has been observed that pests rarely feed on the stems and leaves of wild ginseng, which is highly associated with the content of ginsenosides.…”
Section: Chemical Defense Role Of Ginsenosides In Plantsmentioning
confidence: 99%
See 2 more Smart Citations